METODE ROLE PLAYING DALAM UPAYA MENINGKATKAN PEMAHAMAN DAN MOTIVASI PESERTA DIDIK PEMBELAJARAN KONSEP IKATAN KIMIA - Handayani, Esti; Mery, Mery (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research aims to determine effect of using Role Playing method on increasing motivation to learn the concept of chemical bonds. This research the teacher expected to obtain the right learning method to improve the quality of learning in Class X of MIPA-1 at National SHS 1 Muara Padang, especially in material of Chemical Bonds. With the Role Playing method, students motivation and understanding are supposed to increase and their learning outcomes also increase. Using a class action research model from Kurt Lewin and Kemis & McTagart are carried out in two cycle. The results showed that of the 30 students, when the teacher used the lecture method the results of the evaluation were only 24% that reached the KKM score (65), the first cycle of student learning evaluation results increased to 46% and in the second cycle the results of student evaluations reached 80% who achieved the KKM score and students were more enthusiastic about learning. So, it can be concluded that the Role Playing method can improve students motivation.